2013
DOI: 10.1371/journal.pgen.1003552
|View full text |Cite
|
Sign up to set email alerts
|

NTRK3 Is a Potential Tumor Suppressor Gene Commonly Inactivated by Epigenetic Mechanisms in Colorectal Cancer

Abstract: NTRK3 is a member of the neurotrophin receptor family and regulates cell survival. It appears to be a dependence receptor, and thus has the potential to act as an oncogene or as a tumor suppressor gene. NTRK3 is a receptor for NT-3 and when bound to NT-3 it induces cell survival, but when NT-3 free, it induces apoptosis. We identified aberrantly methylated NTRK3 in colorectal cancers through a genome-wide screen for hypermethylated genes. This discovery led us to assess whether NTRK3 could be a tumor suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 30 publications
9
114
6
Order By: Relevance
“…Our results showed that the overall mean of methylation level in either normal tumor free tissue or CRC tumor tissue samples was high in which there were just two samples with 0% methylation. Although our results are similar to those of Luo et al (41) and obviously NTRK3 promoter methylation is able to discriminate the tumoral samples from normal tumor free samples with acceptable sensitivity and specificity, however, its high level methylation in tumor adjacent tissue suggests that it may start methylation process far before the appearance of any pathological features in cancerous cells. However, this hypothesis should indeed be further analyzed with samples in very initial stages of carcinogenesis.…”
Section: Amplified Region Productsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results showed that the overall mean of methylation level in either normal tumor free tissue or CRC tumor tissue samples was high in which there were just two samples with 0% methylation. Although our results are similar to those of Luo et al (41) and obviously NTRK3 promoter methylation is able to discriminate the tumoral samples from normal tumor free samples with acceptable sensitivity and specificity, however, its high level methylation in tumor adjacent tissue suggests that it may start methylation process far before the appearance of any pathological features in cancerous cells. However, this hypothesis should indeed be further analyzed with samples in very initial stages of carcinogenesis.…”
Section: Amplified Region Productsupporting
confidence: 87%
“…The NTRK3 gene has been recently demonstrated to become hypermethylated and silenced in CRC cell lines, which suggests its role as a tumor suppressor gene in colorectal cancer (41). The present study analyzed NTRK3 promoter methylation in order to determine whether it can act as a biomarker in diagnosis of CRC or not.…”
Section: Amplified Region Productmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, not only DCC, but also more recently other DRs such as UNC5H, TrkC, and CDON, have been shown to be negatively regulated in various cancer types (6,12,13); moreover, the inactivation of DCC, UNC5H, or CDON in mice is associated with tumor progression (6,10,12). The decreased expression of DRs in various tumor types occurs either through loss-of-heterozygosity (LOH), transcriptional or epigenetic regulation (12)(13)(14)(15)(16). CDON expression has recently been shown to be decreased in neuroblastoma and correlated with patient prognosis.…”
Section: Dependence Receptors As Constraints For Tumor Progressionmentioning
confidence: 99%
“…The primer and probe sequences for methylated EVL (NP_057421) and methylated NTRK3 (NM_002530) were designed using ABI PrimerExpress software Version 5.0. 17 (Applied Biosystems, Life Technologies), and synthesized with a FAM reporter. We determined the relative amounts of each sample through a C-LESS-C1 assay, 18 which amplifies the total amount of DNA in a PCR reaction.…”
Section: Methylight Ddpcrmentioning
confidence: 99%